Utilização do farelo de castanha de caju como suplemento alimentar em dietas de ovinos - Costa, Joaquim Bezerra (2012)
The effects of supplementation with cashew nut meal (CNM) for sheep fed Tifton 85 (Cynodon sp.) grass hay as exclusive forage were evaluated on intake, digestibility, nitrogen balance and ingestive behavior of these animals. For this, we used twenty four male sheep, non-castrated, without defined breed and with an initial body weight (BW) of 16.2 + 3.1 kg and they were housed in metabolic cages. The animals received a control diet consisting basically of Tifton 85 hay. The CNM was used as supplementation to diets at three different levels, representing 6, 12 and 18% of the total feed supplied, with six replicates per supplementation level evaluated. The experimental variables were subjected to variance analysis and regression using SAS version 9.1 by the PROC GLM routine. We observed the linear, quadratic and cubic effects from the variance analysis. The regression equations were adjusted when there was a significance level of P<0.05, using SAS PROC REG (9.1). The CNM supplementation did not cause influence on dry matter (DM) and organic matter (OM) intake expressed in g/day (P> 0.05), neutral detergent fiber (NDF) and total carbohydrates (TC) intake expressed in g/day and g/kg BW0,75 (P> 0.05). As for crude protein (CP) intake (P = 0.0137) and ether extract (EE) (P <0.0001) expressed in g/day, and the DM (P = 0.0180) and OM (P = 0.0122) expressed in g/kg BW0,75, was observed influence of CNM supplementation, with increasing linear effect. The digestibility of DM, OM, EE, NDF and CT showed a quadratic effect with the CNM supplementation (P<0.0001). The CP digestibility showed an increasing linear effect with the CNM supplementation to diets (P<0.0001). The CNM supplementation also promoted influence on nitrogen (N) intake (P=0.0137), N retention (P<0.0001) and on the N balance (P=0.0002). The N intake, N retention and N balance showed an increased linear effect with the increasing in the CNM supplementation. For the ingestive behavior, CNM supplementation did not cause significant differences for time spent on eating, ruminating, total chewing time and leisure time (in hours), eating and ruminating efficiency expressed as grams of DM/h grams of NDF/h, number of ruminal bolus per day and number of chews (P>0.05). The number of ruminal bolus per day, was observe an increased linear effect with the CNM supplementation (P=0.0398). However, the time spent for chews per day it was observed a decreased linear effect with the CNM supplementation (P=0.0072). The CNM Supplementation up to 18% of the total diet for sheep fed Tifton 85 hay as roughage exclusive cause an increase for CP and EE intake, and increased the digestibility coefficients of these dietary nutrients. However, for the level of 18% of CNM supplementation there is reduction in digestibility of DM, OM, NDF and TC. Growing sheep fed with grass hay Tifton 85 as only forage source and supplemented with CNM up to 18% of the total diet do not show marked changes in ingestive behavior.